The dada aesthetic in the construction of the free verse in “Chinfonía burguesa” by José Coronel Urtecho and Joaquín Pasos - Hurtado López, César Antonio (2021)
This article studies the elements of Dada aesthetic that shape the free verse in the poem “Chinfonía burguesa” from the theoretical approach of modern versology. It is propounded as a hypothesis that the discursive strategies of Dada imprint, such as the semantic use of space, rhymes, and parallelisms, are updated in the free verse of the authors to propose a critique of bourgeois conceptions from the framework of irrationality. By doing so, the paper explores the scope of Dada aesthetic, its relation with the free verse in Hispanic America and its application within the poem all through a formal and interpretative analysis.